Orthodontics: Principles and Practice - Phulari, B. S. Basavaraj Subhashchandra (Jaypee Brothers Medical Publishers, 2017)
The objective of this book is to introduce the principles and practices of orthodontics. The fascinating field of orthodontics has come a long way since the era of finger pressure and crude wires to the more sophisticated, state-of-art techniques and appliances of today. This book is a humble step towards meeting this enormous challenge of providing an all comprehensive, yet simple-to-understand text for the students of dentistry. The 49 chapters, encompassing 15 sections have been compiled by an impressive bunch of academicians around the world. The chapter, history of orthodontics gives a quick glance at the turning events in the evolution of the first specialty of dentistry. Often asked and considerably difficult concepts such as cephalometrics and model analysis are explained systematically with provision for quick review. Management of different types of malocclusion is narrated in a simple manner with complete case records to support the text. A separate chapter on preclinical orthodontics has been included for the first time which deals with rationale, armamentarium, and step-by-step wire bending procedures. A working classification of basic orthodontic instruments is given with their modes of usage. An accompanying booklet MCQs in orthodontics features over 2,300 multiple choice questions given chapter-wise with answer keys. Furthermore, in each chapter, the questions follow the same order of points given in that particular chapter, thus can act as a very good means of revision of that topic/chapter and at the same time prepares the student for viva voce as well as PG entrance test and other competitive tests.